2010
DOI: 10.1007/s00134-010-2075-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid pentraxin 3 early after subarachnoid hemorrhage is associated with vasospasm

Abstract: Acute increased concentrations of PTX3 in CSF but not in plasma are related to the occurrence of vasospasm, indicating that measurement of CSF PTX3 associated with the clinical evaluation can improve early diagnosis of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…In this context, Zanier [49] investigated the concentrations of PTX3 and its relation with SCV in the plasma and cerebrospinal fluid (CSF) of 38 aSAH patients. PTX3 was elevated in all SAH patients in both plasma and CSF.…”
Section: Neurologymentioning
confidence: 99%
“…In this context, Zanier [49] investigated the concentrations of PTX3 and its relation with SCV in the plasma and cerebrospinal fluid (CSF) of 38 aSAH patients. PTX3 was elevated in all SAH patients in both plasma and CSF.…”
Section: Neurologymentioning
confidence: 99%
“…Several studies have demonstrated a complementmediated inflammatory response in patients with SAH 16,30,31 ; however, a specific role of LCP has never been shown. A significant relationship between CRP levels and outcome (favorable 6,532 vs unfavorable 7,892 ng/mL, p , 0.01) was observed.…”
mentioning
confidence: 99%
“…Clinical management was performed as previously described 16,17 according to international guidelines. A cohort of 39 consecutive patients admitted to the neuro-critical care unit (intensive care unit) with a diagnosis of SAH were prospectively enrolled between 2009 and 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Ryu et al (20) detected that for ischemic stroke patients, the level of PTX3 at the time of presentation is higher in deceased patients compared to living patients. Zanier et al (21) showed that the level of PTX3 reached its highest in plasma and cerebrospinal fluid (CSF) samples in SAH patients during first 48 hours and during development of vasospasm. In our study, it was detected that the levels of PTX3 at the twelfth hour after presentation were statistically and significantly higher in deceased patients compared to living patients of the SAH group (p<0.05).…”
Section: Discussionmentioning
confidence: 99%